เภสัชจลนศาสตร์ประชากรของยาทาโครลิมัสในผู้ป่วยปลูกถ่ายตับ - วิชญ์ภัทร ธรานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This study aims to develop a population pharmacokinetic model of tacrolimus, to estimate the population means pharmacokinetic parameters of tacrolimus and to identify significant clinical factors that could explain pharmacokinetic variability of tacrolimus along 6 months of transplantation in Thai adult liver transplant patients. A total of 1,012 tacrolimus concentrations-time measurements from 50 recipients following Day 8th to Month 6th post-liver transplantation was modeled by nonlinear mixed effects approach using NONMEM and PDx-POP software to perform the population pharmacokinetics analysis. Thirteen relevant covariates were tested to explore their influential effect on pharmacokinetic variability. Pharmacokinetics of oral immediate-release tacrolimus in Thai liver transplant patients is best described by one-compartment model with first order absorption and elimination. The final estimates of apparent clearance (CL/F) and apparent volume of distribution (V/F) of tacrolimus were 26.2 L/h (Interindividual variability; IIV, 40.1%) and 890 L (IIV, 80.3%), respectively.The population pharmacokinetic equation that predicted the CL/F of tacrolimus was CL/F = 26.2 x (hemoglobin (HB)/11) –0.802 x (total bilirubin (TB)/1.9) –0.096. Based on the equation, a higher level of HB and elevated TB would result in decreasing CL/F of tacrolimus during Day 8th to Month 6th in liver transplant patients. None of the tested clinical factors influenced V/F of tacrolimus. The first population pharmacokinetic model of tacrolimus in adult Thai liver transplant patients was initially developed and validated to assist in dosage individualization. HB and TB were significant clinical factors influenced the CL/F of tacrolimus from 8th day to 6th month post-liver transplantation. No clinical factors had influenced on V/F of tacrolimus in this study.